From Zebrafish to humans: in silico comparative study of RAD50 sequences - Nahid Khalili; Ahmed Najm; Mahmood, Ibrahim; Douglas, Law; Chyan, Leong Ng; Ahmad Azfaralariff; Shazrul Fazry (Penerbit Universiti Kebangsaan Malaysia, 2024)
DNA damage, particularly the occurrence of DNA double-strand breaks (DSBs), presents a significant hazard to the integrity and viability of cells. Improper repair of DSBs can result in chromosomal alterations, oncogenic changes, or cell demise. The MRE11-RAD50-NBS1 (MRN) complex plays a crucial role in DNA repair and signaling under the Ataxia Telangiectasia Mutated (ATM) kinase regulation. In this study, we employed comprehensive computational techniques to analyze the structure of RAD50 in Danio rerio (Zebrafish), utilized as a model organism. Additionally, we conducted in silico assessments of RAD50 from both Zebrafish and humans, comparing their characteristics. The substantial sequence resemblance between DrRAD50 and HsRAD50 suggests that DrRAD50 could potentially serve as a valuable model for HsRAD50. However, it is important to acknowledge that sequence similarity alone does not necessarily imply functional equivalence. Further functional studies are needed to confirm the extent of their functional similarities. By examining the secondary and tertiary protein structures of RAD50, we observed a notable likeness between Zebrafish and Human RAD50 proteins. In silico analysis demonstrated that the sequence of RAD50 in zebrafish shares 70% similarity with the human RAD50 protein.